Olfactory Fluctuation Revisited. (1st August 2020) - Hsieh, Julien W.; Daskalou, Dimitrios; Detroux, Valentine; Sipione, Rebecca; Senn, Pascal; Hugentobler, Marianne; Landis, Basile N.
Abstract : Objectives: Many patients complain about olfactory fluctuation (OF), which is a symptom commonly attributed to sinonasal disease. Data‐based evidence for its association with sinonasal disease is scarce. The aim of the study is to identify explanatory variables associated with OF and to analyze its predictive value regarding sinonasal disease. Study design: We performed a retrospective study based on patients with olfactory dysfunction. Methods: We analyzed data from 482 patients attending the smell and taste outpatient clinic with full psychophysical workup and structured questions regarding their symptoms. The questionnaire included items on OF and chronic nasal symptoms. Clinical investigators filled out the second part of this questionnaire that included information about nasal endoscopy, psychophysical tests of orthonasal olfaction (Sniffin' Sticks), retronasal olfaction, and putative etiology of olfactory dysfunction. Results: OF was more prevalent in sinonasal disease (42.4%) compared to other putative etiologies of olfactory dysfunction such as postinfectious (28%) or posttraumatic (11.7%) (X2 [5, n = 440] = 24.98; P < .0001). OF was strongly associated with Sniffin' Sticks score categories (anosmia, hyposmia, normosmia) (X2 [2, n = 424] = 39.21; P < .0001; Cramer's V = 0.30; P < .0001) and presence of "chronic nasal symptoms" (X2 [1, n = 437] = 22.71; P < .0001; Cramer's V = 0.23; P < .0001). The accuracy in predicting putative sinonasal disease etiology when OF was present depended strongly on the clinical context. Conclusion: Olfactory fluctuation is a symptom mostly but not exclusively associated with sinonasal disease, elevated Sniffin' Sticks test scores, and is frequently accompanied by other nasal complaints. Its presence is valuable information for clinicians to be integrated into the clinical context when doing patients' workup. Level of Evidence: 4 Laryngoscope, 130:2442–2447, 2020